Evaluation of the Thermo Scientific SureTect Salmonella Species PCR Assay in a Broad Range of Foods and Select Environmental Surfaces: Pre-Collaborative and Collaborative Study: First Action 2021.02. (29th September 2021) - Bastin, Benjamin; Thompson, Wesley; Benzinger, M Joseph; Crowley, Erin S; Leonte, Ana-Maria; Vandoros, Evangelos J; Thomas, Daniel; Hughes, Annette; Crabtree, David; Evans, Katharine; Sohier, Daniele
Abstract: Background: The Thermo Scientific™ SureTect™ Salmonella species PCR Assay utilizes Solaris™ reagents for performing PCR for the rapid and specific detection of Salmonella species in a broad range of foods and select environmental surfaces. Objective: The aims were to demonstrate the reproducibility of the Thermo Scientific SureTect Salmonella species PCR Assay in a collaborative study using a challenging matrix, cocoa powder, and to extend the scope of the method. Method: In the collaborative study, the candidate method was compared to the US Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM) Chapter 5 Salmonella reference method. The candidate method used two PCR thermocyclers, the Applied Biosystems™ QuantStudio™ 5 Real-Time PCR instrument (QS5) and the Applied Biosystems 7500 Fast Real-Time PCR instrument (7500 Fast). Fourteen participants from nine laboratories located within the United States and Europe were solicited for the collaborative study, with 12 participants submitting valid data. Three levels of contamination were evaluated for each matrix. Statistical analysis was conducted according to the probability of detection statistical model. In addition, 11 matrix studies were performed comparing the candidate method to the FDA/BAM Chapter 5 or US Department of Agriculture, Food Safety and Inspection Service, Microbiology Laboratory Guidebook 4.10 Isolation and Identification of Salmonella from Meat, Poultry, Pasteurized Egg, and Siluriformes (Fish) Products and Carcass and Environmental Sponges reference method. Nine of these matrices were also compared to the EN ISO 6579–1:2017/Amd.1:2020(E) Microbiology of the food chain—Horizontal method for the detection, enumeration and serotyping of Salmonella—Part 1: Detection of Salmonella spp.—AMENDMENT 1: Broader range of incubation temperatures, amendment to the status of Annex D, and correction of the composition of MSRV and SC reference method. Results: In the collaborative study, the difference in laboratory results indicates equivalence between the candidate method and reference method for the matrix evaluated, and the method demonstrated acceptable interlaboratory reproducibility as determined in the collaborative evaluation. False-positive and false-negative rates were determined for the matrix and produced values of <2%. The two PCR thermocyclers (QS5, 7500 Fast) performed equivalently. There were no result differences between candidate method confirmations and reference method confirmations. In the pre-collaborative matrix extension, the results from the matrix studies showed a comparable performance between the candidate method and the tested reference methods. Conclusions: Based on the data generated, the method demonstrated acceptable interlaboratory reproducibility data and statistical analysis. Highlights: Due to the COVID-19 pandemic, some participants had to be trained remotely. Additionally, 375 g cocoa powder is known to be a challenging matrix for PCR methods. No unusual cross-contamination or false-positive/negative was reported, highlighting the ease of use, reproducibility, and robustness of the method.